2016
DOI: 10.1093/hmg/ddw328
|View full text |Cite
|
Sign up to set email alerts
|

Paternal age effects on spermFOXK1andKCNA7methylation and transmission into the next generation

Abstract: Children of older fathers carry an increased risk for developing autism and other disorders. To elucidate the underlying mechanisms, we investigated the correlation of sperm DNA methylation with paternal age and its impact on the epigenome of the offspring. Methylation levels of nine candidate genes and LINE-1 repeats were quantified by bisulfite pyrosequencing in sperm DNA of 162 donors and 191 cord blood samples of resulting children (conceived by IVF/ICSI with the same sperm samples). Four genes showed a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
53
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 61 publications
4
53
0
Order By: Relevance
“…It seemed that ART procedures together with etiological factors, including reduced fertility of the parents or the advanced maternal and paternal age, impact the epigenetic DNA methylation state. Recent studies has found epigenetic variability in the male or female germline, and occurrence of age-related DNA-methylation changes in a number of genes, and those changes may contribute to the increased ASD risk in offspring of older parents383940.…”
Section: Discussionmentioning
confidence: 99%
“…It seemed that ART procedures together with etiological factors, including reduced fertility of the parents or the advanced maternal and paternal age, impact the epigenetic DNA methylation state. Recent studies has found epigenetic variability in the male or female germline, and occurrence of age-related DNA-methylation changes in a number of genes, and those changes may contribute to the increased ASD risk in offspring of older parents383940.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, the sperm epigenome is modified by ageing and obesity . Interestingly, the age‐associated sperm DNA demethylation of the FOXK1 promoter is associated with offspring foetal cord blood methylation and accelerated gene demethylation in autistic youth …”
Section: Epigenetic Inheritance Of Health and Disease Risk: A Focus Omentioning
confidence: 99%
“…100 Interestingly, the age-associated sperm DNA demethylation of the FOXK1 promoter is associated with offspring foetal cord blood methylation and accelerated gene demethylation in autistic youth. 98 It is important to note the difference between transgenerational inheritance and environmental impacts leading to intergenerational or multi-generational inheritance (see Fig. 3).…”
Section: Environmental Insultsmentioning
confidence: 99%
“…To study epigenetic inheritance as a possible mechanism underlying the paternal age effect, Atsem et al [2016] selected DRD4 , NCOR2 , NKX2-5 , KCNA7 , GET4 , DMPK , PDE4C , TNXB , and FOXK1 from a set of genes with age-related changes in DNA methylation because of their association with neuropsychiatric and other disorders [Jenkins et al, 2014]. To calibrate their data, repetitive LINE-1 elements, comprising roughly 17% of the human genome, were used as a surrogate marker for global DNA methylation.…”
mentioning
confidence: 99%
“…In hindsight, such transmitted factors may very well relate to aberrant methylation at specific genomic loci in the brain [Schneider et al, 2012[Schneider et al, , 2014[Schneider et al, , 2016Berko et al, 2014]. Another ramification of the study by Atsem et al [2016] may be possible phenotypic differences in patients with genetic and epigenetic mutations. In ASD patients with or without comorbid conditions, diverse subphenotypic manifestations of CNVs have been inferred and detected [Poot, 2013;Merikangas et al, 2015].…”
mentioning
confidence: 99%